2020
DOI: 10.18421/tem92-03
|View full text |Cite
|
Sign up to set email alerts
|

Changing of the Maintenance System in the Production Plant with the Application of Predictive Maintenance

Abstract: The main goal of this paper is to analyse the current system of maintenance in selected company and after identification of crucial problems, to propose the new system of maintenance that will be built based on predictive maintenance. The paper is divided into three sections. First section treats predictive maintenance in theoretical plane. Second section deals with analysis of current situation in the selected company in the maintenance area, while in this section you can find information about spare parts co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…(P Hybrid-BN ) 0.81 = 6.43031 − 0.231142Cv − 0.092833T + 0.008571Nr − 0.002235CvT − 0.036615CvNr − 0.000215TNr + 0.001038CvTNr (7) Variable from Equations ( 4)-( 7) are as follows: The values calculated by Equations ( 4)-( 7) must be transformed by the Equation ( 8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(P Hybrid-BN ) 0.81 = 6.43031 − 0.231142Cv − 0.092833T + 0.008571Nr − 0.002235CvT − 0.036615CvNr − 0.000215TNr + 0.001038CvTNr (7) Variable from Equations ( 4)-( 7) are as follows: The values calculated by Equations ( 4)-( 7) must be transformed by the Equation ( 8).…”
Section: Resultsmentioning
confidence: 99%
“…After adopting various lean techniques, mainly, value stream mapping, takt time and line balancing, authors reported improvement of assembly line efficiency up to 97%, as well as reductio of lead time about 13%. A similar case study of the application of lean production in small series production company is presented in [7]. After analyzing and eliminating waste, productivity has been improved, as well as lead time [7].…”
Section: Lean and Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The success of modern engineering production strategies is based on the application of new approaches and design methods. It is necessary to solve complex problems of project tasks of which the following is typical [1,4]:…”
Section: Production System Model and Methodological Procedures Of Designingmentioning
confidence: 99%